What role for the 'long arm of childhood' in social gradients in health? An international comparison of high-income contexts. (1st April 2021) - Haas, Steven A.; Zhou, Zhangjun; Oi, Katsuya
Abstract : Social gradients in health have been a focus of research for decades. Two important lines of social gradient research have examined (1) international variation in their magnitude and (2) their life course / developmental antecedents. The present study brings these two strands together to explore the developmental origins of educational gradients in health. We leverage data spanning 14 high-income contexts from the Health and Retirement Study and its sisters in Europe. We find that early-life health and socio-economic status consistently attenuate educational gradients in multimorbidity and functional limitation. However, the relative contribution of early-life factors to gradients varies substantially across contexts. The results suggest that research on social gradients, and population health broadly, would benefit from the unique insights available from a conceptual and empirical approach that integrates comparative and life course perspectives.